2005
DOI: 10.1530/rep.1.00660
|View full text |Cite
|
Sign up to set email alerts
|

What have we learned about gonadotropin function from gonadotropin subunit and receptor knockout mice?

Abstract: A number of biochemical and physiological studies elucidated the roles of pituitary and placental glycoprotein hormones. Advances in the past two decades in manipulating the mouse genome by random or site-specific mutagenesis have heralded a new dimension to our understanding of the biology of gonadotropins. It is now possible to model many human reproductive disorders involving gonadotropins/gonadotropin-signaling in the mouse. Mutant mice selectively lacking either FSH or LH or their cognate receptors have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(54 citation statements)
references
References 94 publications
(79 reference statements)
2
52
0
Order By: Relevance
“…This finding is not surprising as it was reported that an impact on fertility should have an estimated sperm count reduction to 10% or less (22). Furthermore, previous reports have demonstrated several animal models with reduced sperm count but normal fertility (22)(23)(24)(25)(26). ADP-ribosylation factor-like 4 (Arl4) is a GTP-binding protein that shuttles between the nucleus and intracellular organelles depending on GTP͞GDP-binding status.…”
Section: Altered Expression Of Sertoli Cells' Functional Genes Junctmentioning
confidence: 85%
See 1 more Smart Citation
“…This finding is not surprising as it was reported that an impact on fertility should have an estimated sperm count reduction to 10% or less (22). Furthermore, previous reports have demonstrated several animal models with reduced sperm count but normal fertility (22)(23)(24)(25)(26). ADP-ribosylation factor-like 4 (Arl4) is a GTP-binding protein that shuttles between the nucleus and intracellular organelles depending on GTP͞GDP-binding status.…”
Section: Altered Expression Of Sertoli Cells' Functional Genes Junctmentioning
confidence: 85%
“…Schürmann et al (23) have demonstrated that Arl4 null mice have 30% reduction in testis weight and a 60% reduction in sperm count, but do not have a reduction in litter size or frequency. In addition, FSH␤ has been reported to play a role in spermatogenesis and mice lacking FSH␤ are also fertile despite having a reduced testis size and epididymal sperm count (25,26). Furthermore, centromere protein B is a DNA-binding protein required for meiosis, and its deletion caused a reduction in testis weight by 30% and a 40% reduction in sperm count without a reduction in fertility (24).…”
Section: Altered Expression Of Sertoli Cells' Functional Genes Junctmentioning
confidence: 99%
“…Because there were no anatomical differences in reproductive organs among male Cstf2t ϩ/ϩ , Cstf2t ϩ/Ϫ , and Cstf2t Ϫ/Ϫ mice (SI Fig. 5B and Table 2), this suggested that the infertility was not due to major developmental or hormonal blockages in spermatogenesis (14).…”
Section: Male Cstf2t ؊/؊ Mice Are Infertile But Show No Gross Anatomicalmentioning
confidence: 96%
“…Fshb/Fshr null females mostly phenocopy each other and demonstrate a pre-antral stage block in ovarian folliculogenesis (85,86). Lhb/Lhr null females also phenocopy each other and display a pre-ovulatory stage block in ovarian folliculogenesis (69,87,88).…”
Section: Altered Expression Of Transcriptional Activators and Repressmentioning
confidence: 99%
“…Dicer cKO Female Mice Display Fertility Defects-Loss of gonadotropins and their cognate receptors results in impairment of ovarian folliculogenesis at distinct phases of ovarian development (85,86). Fshb/Fshr null females mostly phenocopy each other and demonstrate a pre-antral stage block in ovarian folliculogenesis (85,86).…”
Section: Altered Expression Of Transcriptional Activators and Repressmentioning
confidence: 99%